Chromosome constitution of a hybrid between East African Buffalo (Syncerus caffer caffer) and Dwarf Forest Buffalo (Syncerus caffer nanus) - (:unkn) unknown (My University, 1980)
The chromosome constitution of a male hybrid of first backcross between a female F1 East African X Dwarf African Buffalo (Syncerus caffer caffer X Syncerus caffer nanus) and a male Dwarf Forest Buffalo (Syncerus caffer nanus) had a chromosome number of 53: 21 acrocentric pairs, 2 unpaired acrocentrics, 3 meta-submetacentric pairs, 1 unpaired submetacentric and 1 acrocentric XY sex chromosome pair. The R-banding pattern shows that the chromosomic difference between the subspecies caffer (2n = 54) and nanus (2n = 52) is due to a centric fusion between two acrocentric pairs.
Keywords: African Research